Mindfulness and acceptance-based training for elite adolescent athletes: a mixed-method exploratory study - Su, Ning; Si, Gangyan; Liang, Wei; Bu, Danran; Jiang, Xiaobo (Frontiers in Psychology, 2024)
Objectives This study aimed to examine the effectiveness of a specifically designed mindfulness-acceptance-insight-commitment (MAIC) training program on relevant psychological factors (i.e., mindfulness, acceptance, performance-related satisfaction) as well as sport training performance for elite adolescent athletes from Hong Kong. And it also aimed to explore the athletes’ real experiences (i.e., receptiveness and perceptions) of completing the MAIC program. Methods and design The mixed-method was used in this study, including a randomized controlled trial (RCT) and a qualitative exploration. The RCT employed a 2 (groups) x 3 (data collection points) design involving 40 elite adolescent athletes from the Hong Kong Sports Institute (HKSI). These athletes were randomly assigned to either the MAIC training group (MT; n = 20, Mage = 15.65) or the control group (CG; n = 20, Mage = 15.85) to further test the effectiveness of the MAIC intervention on mindfulness, acceptance, performance-related satisfaction, and sport training performance. Subsequent to the RCT, the qualitative exploration was used to explore the athletes’ real experiences towards the MAIC program. In the qualitative exploration, all athletes who participated in the MAIC program were invited to participate in voluntary semi-structured interviews. Of these, 14 athletes chose to take part in the interviews. The RCT employed a 2×3 mixed-design ANOVA, while thematic analysis was applied to the qualitative exploration. Results The results revealed that the MAIC training program significantly enhanced athletes’ mindfulness, acceptance, satisfaction with performance, and sport training performance. However, these effects diminished at the follow-up assessment compared to post-training. Notably, the acceptance level of MT athletes did not significantly differ from CG athletes at the follow-up assessment. Additionally, the qualitative analysis identified four key dimensions: (a) Attitude towards MAIC training, (b) Reflection on the MAIC learning process, (c) Outcomes of MAIC training, and (d) Recommendations for future MAIC training. Overall, the qualitative findings complemented and reinforced the quantitative results, offering deeper insights into athletes’ experiences and valuable suggestions for further enhancing the MAIC program. Conclusion The findings suggested that the specifically designed MAIC training program in this study effectively enhanced sport training performance and various psychological factors among elite adolescent athletes from Hong Kong. Nevertheless, further investigations are still required to comprehensively evaluate and further develop the MAIC training program.